АНТИОКСИДАНТНЫЕ ДЕЙСТВИЯ ЖЕЛЕЗА (II) С МЕТИОНИНОМ И ИХ ИССЛЕДОВАНИЕ МЕТОДОМ СПИНОВЫХ МЕТОК - Раджабов, Умарали; Мадиномов, Амриддин (Theoretical and experimental chemistry and modern problems of chemical technology, 2023)
It has been established that in the compound of sulphate of iron(II) with methionin when adding ethanol to the solution with the presence of a nitroxyl radical, it is completely restored and affects to the chemical stability of the nitroxyl fragment which indicates a strong property of antioxidants.